2007
DOI: 10.1186/ar2118
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Patient Acceptable Symptom State (PASS) is an absolute threshold proposed for symptomatic variables in osteoarthritis (OA) to determine the point beyond which patients consider themselves well and, as such, are satisfied with treatment. Two large previously reported studies of knee OA have shown that both lumiracoxib and celecoxib were superior to placebo in terms of conventional outcome measures. To assess the clinical relevance of these results from the patient's perspective, the same data pooled from these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 4 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…The PASS provides clinically meaningful information that can be expressed as a percentage of individuals who meet the threshold for PASS, regardless of the change from baseline in symptoms. 20 Success on the GROC was reported at a higher frequency in the manual therapy-plus-exercise group at the end of care (4 weeks) and at a 6-month longterm follow-up (FIGURE 2). The GROC is commonly utilized in clinical research to determine cutoff scores for patient-perceived changes in condition.…”
Section: Discussionmentioning
confidence: 93%
“…The PASS provides clinically meaningful information that can be expressed as a percentage of individuals who meet the threshold for PASS, regardless of the change from baseline in symptoms. 20 Success on the GROC was reported at a higher frequency in the manual therapy-plus-exercise group at the end of care (4 weeks) and at a 6-month longterm follow-up (FIGURE 2). The GROC is commonly utilized in clinical research to determine cutoff scores for patient-perceived changes in condition.…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that PASS may be more robust than MCII, since it is not affected by initial level of symptoms 61 ; it also has the advantage of encompassing a notion of quality of life. 62 Further research is necessary, though the two techniques, MCII and PASS, do appear to be complementary.…”
Section: 0 Responders In Osteoarthritismentioning
confidence: 99%
“…Firstly, some of the psychological questionnaires (AAQ-II [ 47 ], CPAQ-8 [ 48 ], GIC [ 49 ]) were removed as all the patients had difficulty understanding resulting in completion difficulty. Other outcome measures such as the PAM, Global Perceived Effect (GPE) [ 49 ], Patient Acceptable Symptom State (PASS) and treatment failure [ 66 ] which are sensitive but simple questionnaires will be included for the subsequent RCT in place of the excluded questionnaires as these outcome measures have previously been used in musculoskeletal conditions of the knee [ 67 ]. The overall respondent burden would be reduced.…”
Section: Discussionmentioning
confidence: 99%